2005
DOI: 10.1007/s00420-005-0052-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of short- and long-term unemployment on physical work capacity and on serum cortisol

Abstract: Unemployment has a negative effect on physical working capacity and mental health, depending on the duration of unemployment. Factors that facilitate or impede physical and mental health during unemployment should be identified in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 21 publications
3
41
0
1
Order By: Relevance
“…The two metaanalyses differ in their findings on the effects of duration of unemployment: Brown et al (12) found no significant trend, while Paul and Moser (9, e4) found a linear increase in problems with duration of unemployment. Individual original studies also confirm an increase in problems (13)(14)(15).…”
Section: Total Mortalitymentioning
confidence: 79%
“…The two metaanalyses differ in their findings on the effects of duration of unemployment: Brown et al (12) found no significant trend, while Paul and Moser (9, e4) found a linear increase in problems with duration of unemployment. Individual original studies also confirm an increase in problems (13)(14)(15).…”
Section: Total Mortalitymentioning
confidence: 79%
“…Griep et al 2013;Maier et al 2006) when labelling those individuals that were unemployed for less than 12 months as short-term unemployed. However, some of the subjective complaints load indicators-such as irregular heartbeats and over-perspiration-might require more time to manifest themselves as a consequences of becoming unemployed, whereas psychological well-being indicators might be impacted immediately or in the short-term after becoming unemployed (e.g.…”
Section: Limitationsmentioning
confidence: 99%
“…In line with the suggestions from the ILO (2000) and previous studies on employment in the field of life sciences (e.g. Maier et al 2006) and social sciences (e.g. Griep et al 2013), we chose a cut-off value of 12 months for long-term unemployment.…”
mentioning
confidence: 99%
“…Unemployment has been shown to affect negatively physical working capacity [6] and to increase risk of longterm sickness absence [7]. It has also been suggested that unemployment causes psychological disturbance [8][9][10], minor psychiatric morbidity [11], and depression [12,13].…”
Section: Introductionmentioning
confidence: 99%